Analisis Yuridis Tentang Pemutusan Hubungan Kerja Berdasarkan Undang – Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan Dan Undang – Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Nur Ardini Rahmadani; Lalu Hadi Adha (Fakultas Hukum Universitas Mataram, 2022)
This research aims to compare the regulation of the termination of employment relationship between the Law No. 13 of 2003 on employment and the Law No. 11 of 2020 on job creation. This is a normative legal research which applies statutory, conceptual, and Sosiological approaches.This research finds out that the Law No. 13 of 2003 on employment narrows the space for employers to terminate the employment relationship. On the other hands, the Law No. 11 of 2020 on job creation as stipulates in Article 81 Point 37 amendments to Article 151 paragraph (2) wider space for employers to terminate the employment relationship unilaterally only by giving the labor a notice on the reason of such termination without any confirmation from LPPHI. Regarding labor’s rights, Article 156 of Law Number 13 of 2003 stipulate that the awarding severance payment, long service pay, and compensation for entitlements are in accordance with existing laws and regulations.